Bis-(3'-5')-cyclic dimeric GMP regulates antimicrobial peptide resistance in pseudomonas aeruginosa - Chua, Song Lin (2015)
Bis-(3′-5′)-cyclic dimeric GMP (c-di-GMP) is an intracellular second messenger that controls the lifestyles of many bacteria. A high intracellular level of c-di-GMP induces a biofilm lifestyle, whereas a low intracellular level of c-di-GMP stimulates dispersal of biofilms and promotes a planktonic lifestyle. Here, we used the expression of different reporters to show that planktonic cells, biofilm cells, and cells dispersed from biofilms (DCells) had distinct intracellular c-di-GMP levels. Proteomics analysis showed that the low intracellular c-di-GMP level of DCells induced the expression of proteins required for the virulence and development of antimicrobial peptide resistance in Pseudomonas aeruginosa. In accordance with this, P. aeruginosa cells with low c-di-GMP levels were found to be more resistant to colistin than P. aeruginosa cells with high c-di-GMP levels. This finding contradicts the current dogma stating that dispersed cells are inevitably more susceptible to antibiotics than their sessile counterparts.